Auction Format Matters : Evidenceon Bidding Behavior and Seller Revenue - Feldman, Robert; Reinhart, Vincent (Washington, D.C. : International Monetary Fund, 1995)
This paper evaluates the importance of auction format on bidding behavior and seller revenue, focusing on differences in performance under uniform-price and discriminatory-price formats. The analysis is based on a standard benchmark model from which empirically-testable hypotheses are derived on the optimal amount of bid shading that generates revenue equivalence between the two formats. Applying this model to data from the IMF gold auctions run in 1976-80, we find evidence of statistically significant shading in excess of the theoretically-derived optimum under the discriminatory format. This evidence suggests greater seller revenue under the uniform-price format.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Auction Format; Discriminatory-Price Auction; Price; Uniform-Price Auction; WP; United States